Sukuk Innovation and Blockchain Integration: Sustainable Social, Economic and Environmental Based Financing - Febrianto, M. Nanang; Asshidqi, Ahmad Fauzi; Adlan, Muhamad Aqim (Al-Infaq: Jurnal Ekonomi Islam, 2025)
Sukuk issuance encourages development and increases Muslim preferences in investing and addresses the challenges of the sharia-based financing gap. The purpose of this study is to explore sukuk innovation and blockchain integration to support social, economic, and environmental-based financing implemented in Islamic countries. Literature studies were conducted by tracing previous studies, such as national and international indexed articles, reports from institutions, and books relevant to sukuk. The results obtained, the difference between sukuk and bonds refers to sukuk as proof of ownership of assets (underlaying) and is based on sharia principles. Environmental-based financing innovation supports renewable energy, climate mitigation, technological innovation using green sukuk financing, blue sukuk, and sustainable sukuk. As well as sukuk Ihsan, sukuk peduli, and sukuk waqf as social and economic based financing in poverty alleviation, inequality, and public infrastructure development. The development of financial technology and blockchain supports sukuk transformation through smart sukuk, increasing transparency, accountability, and efficiency of procedures and costs has been implemented by Blossom Finance Indonesia, Finterra Malaysia, and Wethaq Dubai.